WORK-LIFE BALANCE ANALYSIS OF WOMEN'S EMPLOYMENT IN INFORMATION TECHNOLOGY - Ayswarya B.M; M. Jagathish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The work schedules of IT sector personnel have grown increasingly demanding in the recent technological era, making it difficult for them to maintain a work-life balance. Since globalization has been the norm, it appears that these kinds of challenges have been neglected for some time. Over time, concerns about the "imbalance" between work and personal life have grown due to growing health issues, decreased employee productivity and efficiency, and workplace boredom. The disparity also has an unsettling effect on working people's personal lives, with some developing into societal dangers including infertility brought on by high stress levels, an increase in divorces, and the start of nuclear families. Professionals nowadays seem to be more engaged in their profession, which allows them greater flexibility in the workplace. The demands of the working community vary depending on their stage of life. People thus try to strike a balance between their personal and professional obligations. Because work-life balance provides clear advantages for both businesses and their people, it has grown in importance in recent years. Companies may now concentrate on developing their staff members, who are increasingly seen as the organization's human capital rather to just as workers. This may serve as a significant motivator and aid in keeping employees for a considerable amount of time.